An Empirical Evaluation of a Historical Data Warehouse - Neil, Carlos (2013)
Computing is widely regarded as a scientific discipline that emphasizes on three different perspectives: mathematics, present in the development of formalisms, theories and algorithms; engineering, linked to the goal of making things better, faster, smaller, cheaper and, finally, the science that can be defined as the activity to develop general and predictive theories that allow these theories to be evaluated and tested. However, research in software engineering rarely describes explicitly its research paradigms and standards to assess the quality of its results. Due to a growing understanding in the computer science community that empirical studies are needed to improve processes, methods and tools for the development and maintenance of software, an emerging area in software engineering is developed: the Empirical Software Engineering. This subarea is one step down in the claims of scientificity but it aims to address this shortcoming. The objective of this work is to conduct an empirical corroboration for developing a method of a Historical Data Warehouse, the temporal data model and the associated query interface.